The WTO must bounce back - Stuart Harbinson (European Centre for International Political Economy (ECIPE), 2012)
This policy brief surveys the state of the multilateral trading system, tracing the gradual decline of the Doha Round negotiations and the emergence of new regional and plurilateral initiatives. It concludes that the model of the negotiations followed in the Round in recent years has been overtaken by events. It is however at this stage not clear whether the new initiatives now being pursued outside the WTO will have a catalytic effect on the multilateral trading system or will fragment it. There is a danger of squandering the legacy so painstakingly built up in the GATT and the early years of the WTO, which have contributed to decades of orderly and peaceful economic growth. For this reason it is vital that governments urgently take steps to rebuild confidence in the WTO. This confidence can be restored through governments committing themselves to a strategic dialogue leading to a new consensus on the objectives and general principles underpinning their activities in the WTO.
Keywords: 330; WTO-Verhandlungen